Protective effects of alginate–chitosan microspheres loaded with alkaloids from Coptis chinensis Franch. and Evodia rutaecarpa (Juss.) Benth. (Zuojin Pill) against ethanol-induced acute gastric mucosal injury in rats - Wang QS; Zhu XN; Jiang HL; Wang GF; Cui YL (Dove Medical Press, 2015)
Qiang-Song Wang,1,2,* Xiao-Ning Zhu,1,* Heng-Li Jiang,1,* Gui-Fang Wang,3 Yuan-Lu Cui1 1Tianjin State Key Laboratory of Modern Chinese Medicine, Research Center of Traditional Chinese Medicine, Tianjin University of Traditional Chinese Medicine, 2Institute of Biomedical Engineering, Chinese Academy of Medical Science & Peking Union Medical College, 3Pharmacy Department, Baokang Hospital, Tianjin University of Traditional Chinese Medicine, Tianjin, People’s Republic of China *These authors contributed equally to this work Abstract: Zuojin Pill (ZJP), a traditional Chinese medicine formula, consists of Coptis chinensis Franch. and Evodia rutaecarpa (Juss.) Benth. in a ratio of 6:1 (w/w) and was first recorded in “Danxi’s experiential therapy” for treating gastrointestinal disorders in the 15th century. However, the poor solubility of alkaloids from ZJP restricted the protective effect in treating gastritis and gastric ulcer. The aim of the study was to investigate the protective mechanism of mucoadhesive microspheres loaded with alkaloids from C. chinensis Franch. and E. rutaecarpa (Juss.) Benth. on ethanol-induced acute gastric mucosal injury in rats. Surface morphology, particle size, drug loading, encapsulation efficiency, in vitro drug release, mucoadhesiveness, and fluorescent imaging of the microspheres in gastrointestinal tract were studied. The results showed that the mucoadhesive microspheres loaded with alkaloids could sustain the release of drugs beyond 12 hours and had gastric mucoadhesive property with 82.63% retention rate in vitro. The fluorescence tracer indicated high retention of mucoadhesive microspheres within 12 hours in vivo. The mucoadhesive microspheres loaded with alkaloids could reduce the gastric injury by decreasing the mucosal lesion index, increasing the percentage of inhibition and increasing the amount of mucus in the gastric mucosa in an ethanol-induced gastric mucosal injury rat model. Moreover, the mucoadhesive microspheres loaded with alkaloids reduce the inflammatory response by decreasing the levels of tumor necrosis factor-α (TNF-α), interleukin 1β (IL-1β), downregulating the mRNA expression of inducible nitric oxide synthase, TNF-α, and IL-1β in gastric mucosa. All the results indicate that mucoadhesive microspheres loaded with alkaloids could not only increase the residence time of alkaloids in rat stomach, but also exert gastroprotective effects through reducing the inflammatory response on ethanol-induced gastric mucosal damage. Thus, these microspheres could be developed as a potential controlled release drug for treatment of gastric ulcer. Keywords: alkaloids, mucoadhesive microspheres, alginate, chitosan, anti-inflammatory, gastric mucosal injury